Teachers’ digital competencies in higher education: a systematic literature review - Basilotta-Gómez-Pablos, Verónica; Matarranz, María; Casado-Aranda, Luis-Alberto; Otto, Ana (International Journal of Educational Technology in Higher Education, 2022)
Digital competence has gained a strong prominence in the educational context, being one of the key competencies that teachers must master in today's society. Although most models and frameworks focus on the pre-university level, there is a growing interest in knowing the state of digital competencies of university teachers, that is, the set of knowledge, skills and attitudes necessary for a teacher to make effective use of technologies. The aim of this research is to present a systematic review of the literature in the Web of Science and Scopus, to identify, analyze and classify the published articles between 2000 and 2021 on digital competences, and thus find and improve the research being done on digital skills and future avenues of teachers in the university context. The SciMAT software is used in the analysis. The initial search reveals more than 343 articles in English, of which 152 are duplicates and 135 are not related to the topic of study. After this filtering, 56 articles are obtained and analyzed in depth. The results reveal a predominance of research that focuses on analyzing teachers' self-assessment and reflection of their digital competencies. Teachers recognize that they have a low or medium–low digital competence, as well as the absence of certain competencies, especially those related to the evaluation of educational practice. Despite the multiple studies that address this issue, it is necessary to continue improving research in this area, deepening the assessment of teachers' digital competencies and design, on this basis, more practical and personalized training programs that respond to the needs of teachers in the digital era.